ANALISIS IMPLEMENTASI PROGRAM KALI BERSIH DI KOTA PEKALONGAN - Muhammad Syarif Hidayat; Puji Astuti; Lusia Astrika (Journal of Politic and Government Studies, 2015)
ABSTRACTIONEntering the era of globalization is rapidly growing industry. Industrial development in Indonesia makes the rate of economic growth increased. Unfortunately it is not accompanied by public awareness of pollution. One area that is facing the problem of environmental pollution is Pekalongan. Very interesting look at the phenomenan that occur in Pekalongan, where the majority of people there depend on the industry, especially batik industry, but on the other hand they face the threat of environmental pollution can disrupt the life of society itself. Given the vital role and function of river in daily life of man, Pekalongan city government implement the Clean River Program referring to the environment minister’s decision No.35 of 1995 on the Clean River Program. Purpose of this study is to see how the development of Clean River Program in the already executed and any obstacles encountered in the implementation.This study used qualitative research methods and design research is qualitative descripttive. Research site here is Pekalongan, while the research subject is the Environment Agency, industry, and the people living around the river. The primary daata sourcce was obtained through interviews and secondary data sources obtained from journals, archives, documents, and others. Quality of data in this study were obtained through analysis of credibility and authenticity of reality. It is also through context analysis of historical background, social, cultural, economic, and political.The results showed Clean River Program implementation in Pekalongan were nice but not maximized. So far the main target of three new to were achieved. That has been reached is the reduction of waste load and strengthening the institusional system, while not yet achieved is to increase the quality of river water. First is tchnical obstacle, namely lack pf public awareness and the housing industry in protecting the environment, especially rivers. Second is geographical constraints, availability of land to build Wastewater Treatment and land surface is too flat complicates waste disposal.Recommendations for The Environment Agency is improving monitoring inspection, perform law enforcement for violating the provisions industry, improving inter-agency coordination, seek development Wastewater Treatment evenly. Recommendations for the industry is often followed socialization, began to build his own Wastewater Treatment, in cooperation with other industries, forming an industry association. While the recommendation for people is often followed socialization, increasing environmental awareness, stop throwing garbage in the river, pften doing voluntary work to clean the river.Keywords: Clean River Program, Wastewater Treatment, River Pollution